“Everyday psychosis” or cognitive biases as dysfunctional ways of processing information in schizophrenia. Case study - Murawiec, Sławomir (Psychiatria Spersonalizowana / Personalized Psychiatry, 2024)
Persons diagnosed with schizophrenia show some specific disturbances in their daily lives in the way they interpret signals from the environment, especially social signals. According to cognitive theories, specific cognitive attitudes, characterised by a tendency to search for interpersonal threats and external attributions, may be key to the risk of psychosis. Taking these cognitive tendencies into account may explaining to some extend the development of psychotic disorders, especially delusions. Cognitive models of psychotic symptoms suggest that delusions and hallucinations can be sustained by biasing attention towards negative or threatening stimuli, and that abnormal emotion processing is associated with the onset of psychosis. In these models, an attentional bias towards negative (or ambiguous, but perceived as negative or threatening) stimuli leads to the persistence of anxiety and drives delusional interpretations. In a conference speech, the author of this work referred to these phenomena as ‘everyday psychosis’. This paper discusses a therapy session in the course of long-term psychotherapy with a patient with schizophrenia. The content revealed during this session may illustrate the phenomena described above.